2021
DOI: 10.1007/s13365-021-00998-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of COVID-19 biology, diagnostics, therapeutics, and disease impacting the central nervous system

Abstract: Graphical abstract The ongoing COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a highly transmissible disease. SARS-CoV-2 is estimated to have infected over 153 million people and to have caused over 3.2 million global deaths since its emergence in December 2019. SARS-CoV-2 is the seventh coronavirus known to infect humans, and like other coronaviruses, SARS-CoV-2 infection is characterized by a variety of symptoms including general flu-like symptoms suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 239 publications
(328 reference statements)
0
18
0
Order By: Relevance
“…SARS-CoV-2 has the potential of causing a cytokine release and triggering an excessive immune response in the periphery ( Wan et al, 2021 ). Such processes might affect the BBB permeability, thus, allowing infected immune cells or the virus per se to invade the CNS and induce a secondary cytokine storm ( Williams et al, 2021 ). Interestingly, increased proinflammatory cytokines and a high titre of anti-SARS-CoV-2 IgG antibodies were detected in the CSF of patient 9, which is a previously described, although rare phenomenon ( Lewis et al, 2021 ).…”
Section: Post-covid-19 Cases Of Parkinsonismmentioning
confidence: 99%
“…SARS-CoV-2 has the potential of causing a cytokine release and triggering an excessive immune response in the periphery ( Wan et al, 2021 ). Such processes might affect the BBB permeability, thus, allowing infected immune cells or the virus per se to invade the CNS and induce a secondary cytokine storm ( Williams et al, 2021 ). Interestingly, increased proinflammatory cytokines and a high titre of anti-SARS-CoV-2 IgG antibodies were detected in the CSF of patient 9, which is a previously described, although rare phenomenon ( Lewis et al, 2021 ).…”
Section: Post-covid-19 Cases Of Parkinsonismmentioning
confidence: 99%
“… 54 This population of immune cells might induce a secondary cytokine storm inside the brain. 44 Interestingly, increased proinflammatory cytokines and a high titer of anti‐SARS‐CoV‐2 IgG antibodies were detected in the CSF of patient 9, which is a previously described, although rare phenomenon. 55 Whether these antibodies were produced locally or crossed the BBB due to the systemic inflammation remains unclear.…”
Section: Discussionmentioning
confidence: 77%
“… 42 A few molecules/ receptors have been speculated to facilitate the SARS‐CoV‐2 entry and spread in the CNS, including ACE2, Transmembrane Serine Protease 2 (TMPRSS2) and Neuropilin 1 (NRP1), with the former being the most, allegedly, common target. 43 ACE2 is highly expressed in the alveolar epithelial type II cells, but is also found in numerous extrapulmonary tissues, such as the vascular and the intestinal endothelial cells and the brain, 44 including the striatum. 45 Using next generation sequencing techniques, ACE2 has been recently detected in the substantia nigra and the olfactory bulb, 46 while autopsy studies have also confirmed a high expression of NRP1 in the olfactory epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…With both respiratory and gastrointestinal symptoms being quite common in the context of Covid-19 ( Cares-Marambio et al, 2021 ; Groff et al, 2021 ) and ACE2 being highly expressed in the alveolar epithelial type II cells and the intestinal endothelial cells ( Williams et al, 2021 ), some researchers have suggested the potential of SARS-CoV-2 entry through the intestine ( Lehmann et al, 2021 ; Mönkemüller, Fry, & Rickes, 2020 ; Zhang et al, 2020 ). RNA of the SARS-CoV-2 has been identified in stool samples and rectal swabs, even in cases with negative nasopharyngeal swabs ( Tang, Schmitz, Persing, & Stratton, 2020 ).…”
Section: Peripheral Pathways That May Contribute To Neuroinflammationmentioning
confidence: 99%
“…On the other hand, a SARS-CoV-2 infection can cause an excessive systemic inflammatory response after triggering a cytokine storm in the periphery, resulting in a BBB disruption ( Sulzer et al, 2020 ). Researchers have suggested that SARS-CoV-2 may infect immune cells, using them as a “trojan horse” to invade the CNS via the impaired BBB or activate different populations of immune cells, which may infiltrate the CNS, causing a secondary cytokine storm and thus neurologic manifestations ( Pezzini & Padovani, 2020 ; Wan et al, 2021 ; Williams et al, 2021 ).…”
Section: Peripheral Pathways That May Contribute To Neuroinflammationmentioning
confidence: 99%